2017
DOI: 10.1186/s12992-017-0233-9
|View full text |Cite
|
Sign up to set email alerts
|

Global research trends of World Health Organization’s top eight emerging pathogens

Abstract: BackgroundOn December 8th, 2015, World Health Organization published a priority list of eight pathogens expected to cause severe outbreaks in the near future. To better understand global research trends and characteristics of publications on these emerging pathogens, we carried out this bibliometric study hoping to contribute to global awareness and preparedness toward this topic.MethodScopus database was searched for the following pathogens/infectious diseases: Ebola, Marburg, Lassa, Rift valley, Crimean-Cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 123 publications
1
137
1
3
Order By: Relevance
“…This is in contrast to systematic review in which duplicate documents are usually present because of the use of different databases. In bibliometric analysis, the retrieved documents need to be checked for the presence of false‐positive results . In the current study, false‐positive results were identified by screening and manually reviewing 10% of the retrieved documents, usually the top‐cited articles.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to systematic review in which duplicate documents are usually present because of the use of different databases. In bibliometric analysis, the retrieved documents need to be checked for the presence of false‐positive results . In the current study, false‐positive results were identified by screening and manually reviewing 10% of the retrieved documents, usually the top‐cited articles.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered a global health priority by the World Health Organization and has pandemic potential because of its zoonotic nature, human-to-human transmissibility, wide geographic distribution of bat reservoir species, high case-fatality rate in humans, and lack of available vaccine or therapeutic agents ( 1 ). Although NiV or NiV-related infections have been demonstrated by serologic surveillance or PCR detection in several bat species across extensive areas, attempts to isolate live NiV have been unsuccessful; there have been only 3 successful reports: Pteropus hypomelanus bats ( 2 ) and P. vapmyrus bats ( 3 ) in Malaysia and P. lylei bats in Cambodia ( 4 ).…”
mentioning
confidence: 99%
“…50 On the other hand, SARS has been the focus of 3379 publications, given the wider time frame of these studies when compared with those of MERS-CoV as a crude explanation. 51 Moreover, the awareness of the global community to the importance of research in controlling and preventing novel infectious diseases was clearly manifested in WHO's list of top emerging diseases with epidemic potential; in which MERS ranked 5 th and SARS ranked 6 th . …”
Section: Global Lessons Learned From Merscov's Cousin Sarsmentioning
confidence: 99%